Evaluating the Adoption of Education-Based Information System Using Extended Technology Acceptance Model (TAM) - K. Kejaletchimy, Karuppiah (2010)
The aim of this study was to evaluate teachers' acceptance of Student Information System (SMM) and Examination Analysis System (SAP). The research model created based on prior research to address the factors of perceived usefulness (PU), perceived ease of use (PEOU), IT literacy level, information richness, product offering, complexity and facilitating conditions towards intention to use and actual use of these systems. Based on the previous study, Augmented Technology Acceptance Model (TAM) has been to determine the teachers intention to use SMM and SAP. This study has been carried out in primary schools in Kota Setar, Kedah Darulaman as case studies. Questionnaire has been used as instrument in this descriptive survey method and the raw data is preprocessed and analyzed using statistical analysis. Statistical analysis software (PASW SPSS 18.0) were used to analyze the primary data using descriptive analysis including cross-tabulation, chi-square and logistic regression analysis. The results from the statistical analysis indicate the significant contribution of these independent variables towards intention to use these systems. Thus, this analysis reveals that there are six factors significantly contribute and influence the intention to use SMM and SAP in education institution.